2020
DOI: 10.1002/smll.202004129
|View full text |Cite
|
Sign up to set email alerts
|

High Carbonization Temperature to Trigger Enzyme Mimicking Activities of Silk‐Derived Nanosheets

Abstract: Since Fe 3 O 4 nanoparticles were first reported to possess intrinsic peroxidase-like activity in 2007, [1] tremendous efforts have been made to constructing nanozymes. They can imitate the extraordinary activities of natural enzymes in biocatalytic chemistry and overcome their shortcomings like poor stability and high cost. [2-5]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Near-infrared (NIR) photo-triggered cancer treatments (phototherapy), typically including photodynamic therapy (PDT) and photothermal therapy (PTT), have attracted extensive interest due to their remarkable effect on synergistic cancer therapy 1 , 2 , 3 , 4 , 5 . Compared with conventional strategies, for example, chemotherapy, near-infrared light-activated therapy demonstrates reduced side effects, minimally invasive nature, and higher spatiotemporal selectivity for precisely controlled promising oncotherapy 6 , 7 , 8 . However, phototherapy would trigger a stress response in living cells, which serves as a survival mechanism to relieve the induced oxidative/heat stress and damage for improving survival of cancer cells in harsh microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Near-infrared (NIR) photo-triggered cancer treatments (phototherapy), typically including photodynamic therapy (PDT) and photothermal therapy (PTT), have attracted extensive interest due to their remarkable effect on synergistic cancer therapy 1 , 2 , 3 , 4 , 5 . Compared with conventional strategies, for example, chemotherapy, near-infrared light-activated therapy demonstrates reduced side effects, minimally invasive nature, and higher spatiotemporal selectivity for precisely controlled promising oncotherapy 6 , 7 , 8 . However, phototherapy would trigger a stress response in living cells, which serves as a survival mechanism to relieve the induced oxidative/heat stress and damage for improving survival of cancer cells in harsh microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various carbon materials have been used in different photothermal applications such as solar steam generation, photothermal therapy and so on. 19,[39][40][41][42][43][44][45][46][47][48] It was reported that coupling a photothermal material with a photocatalyst could change the spontaneous charge migration to electric field-guided charge transfer for enhanced catalytic performance, due to the formation of an electric near-field at the junction of the two components. 49 Herein, a novel hollow nitrogen doped carbon@ZnIn 2 S 4 (HNC@ZIS) was fabricated for photothermal accelerated photocatalysis (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the typically employed fabrication methods of heteroatom-doped GO nanozymes usually requires the metal catalyst-assisted GO presynthesis and then time-consuming and multistep heteroatom-doping processes that occurred post-GO formation, , which may be challenged by some disadvantages like the harsh conditions (i.e., high temperature/pressure), complicated procedures, and unavoidable impurities introduction. However, the direct pyrolysis of heteroatom-containing organic or biomolecules ,, employed in the synthesis of a carbon-based nanozyme may provide a more facile, green, and low-cost fabrication approach for a GO nanozyme.…”
Section: Introductionmentioning
confidence: 99%